Erdheim‐Chester Disease and Langerhans Cell Histiocytosis: A Case of Overlap Syndrome. (17th November 2020) - Ippolito, Davide; Ragusi, Maria; Maino, Cesare; Pecorelli, Anna; Giandola, Teresa; Franzesi, Cammillo Talei; Sironi, Sandro
Abstract : Only 500 cases of Erdheim‐Chester disease have been reported in the literature to date. To increase awareness of this rare disease, this letter to the editor describes the unusual case of a woman who was diagnosed with mixed histiocytosis: Erdheim‐Chester disease and Langerhans cell histiocytosis.